Allyl isothiocyanate – An alternative biofumigant to manage post-harvest losses - Renuka, V V L; Patil, B Naveenkumar; Gowda, G Basana; Pandi, Guru P; Adak, Totan (Indian Farming, 2019)
Allyl isothiocyanate (AITC), a bio-fumigant obtained from Brassicaceae family, is a potential alternative to synthetic pesticides in controlling the fungi, bacteria and insect-pests during storage. LC50 values of AITC against various stored grain insect-pests i.e. Sitophilus oryzae, S. zeamais, Tribolium spp, Rhyzopertha dominica, etc. were reported to be around 0.5 to 5.5 μl/L and the Minimum Inhibitory and Bactericidal Concentration values against different fungi and bacteria were around 60 to 180 μg/mL, thus proving its antimicrobial property. Different innovative formulations like encapsulation and nano-emulsions of this compound have been emerging which makes it more effective and feasible for use. Chemical fumigants were discouraged due to their health impacts to human and environment, AITC can be a better alternative as an eco-friendly biofumigant.